Relation Between Iron Deficiency Anemia and Inflammatory Marker in Female of Assam downtown University: With Reference to Body Weight - hallam, Liangsi; bariam, Rabina; Das, Anamika; Ahmed, Iftikhar; Nath, Sunit (Journal of Neonatal Surgery, 2025)
This study explores the relationship between iron deficiency anemia, inflammatory markers, and body weight among female students at Assam down town University. Despite high awareness of iron deficiency, only 9% reported using iron supplements, indicating a gap between knowledge and health behavior. Anthropometric and hematological assessments revealed wide variability in BMI, hemoglobin, and iron levels, with evidence of both underweight and obese individuals. Inflammatory markers such as Erythrocyte Sedimentation Rate (ESR) and C-reactive protein (CRP) showed significant associations with higher body weight, suggesting increased inflammation in overweight and obese participants. A positive correlation between age, BMI, and ESR further supports the link between weight and systemic inflammation. These findings underscore the need for targeted interventions focusing on weight management, regular screening, and improved health education to address iron deficiency anemia and its associated inflammatory risks